Postpartum PTSD and birth experience in Russian-speaking women. (September 2022) - Yakupova, Vera; Suarez, Anna
Abstract: Objective: The principal goal of this study was to examine risk factors for postpartum posttraumatic stress disorder (PTSD), such as mode of birth, obstetric violence and medical interventions during labor, in Russia. This study is also the first attempt to investigate the association between the support during labor and postpartum PTSD in a Russian sample. Research design: 611 Russian-speaking mothers aged 18 to 45 years ( M  = 31.2 + 4.5) filled in the online form, which included Edinburgh Postnatal Depression Scale, the City Birth Trauma Scale and survey on demographic characteristics and childbirth experience within one year after birth. Findings: Among the participants 45.7% had clinically significant depressive symptoms and 15% fulfilled all the diagnostic criteria for PTSD. Postpartum PTSD symptoms were higher among women who had a cesarean vs vaginal birth ( p  = 0.009), women with medical interventions ( p  = 0.043) and women who experienced obstetric violence ( p  < 0.001) during childbirth. The more interventions they had and the more instances of obstetric violence they experienced, the higher were the PTSD symptoms ( B  = 1.03, 95% CI 0.23; 1.84, p  = 0.012 and B  = 5.08, 95% CI 3.80; 6.37, p  < 0.001, respectively). The presence of a partner or a personal midwife/doula at birth was associated with lower rates of cesarean birth, fewer medical interventions and less obstetric violence ( p  <  0.017 for all). Key conclusions: Postpartum PTSD is widespread in Russia, and the problem of obstetric violence and overuse of medical interventions has a systematic nature. Increased availability of individual continuous support during labor and the development of professional midwife and doula communities might be a potential avenue to address these problems. Implications for practice: Our findings emphasize the importance of ethics in patient-doctor communication in the maternal healthcare system and the role of support during labor, which is still not widely available in Russia.